Review paperCat-scratch disease: a wide spectrum of clinical pictures - Mazur, Katarzyna; Mania, Anna; Kemnitz, Paweł; Figlerowicz, Magdalena; Służewski, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
The aim of this review is to present an emerging zoonotic disease caused by Bartonella henselae . The wide spectrum of diseases connected with these bacteria varies from asymptomatic cases, to skin inflammation, fever of unknown origin, lymphadenopathy, eye disorders, encephalitis and endocarditis. The reservoirs of B. henselaee are domestic animals like cats, guinea pigs, rabbits and occasionally dogs. Diagnosis is most often based on a history of exposure to cats and a serologic test with high titres of the immunoglobulin G antibody to B. henselaee . Most cases of cat-scratch disease are self-limited and do not require antibiotic treatment. If an antibiotic is chosen, however, azithromycin has been shown to speed recovery.